Toxicity Studies on Novel N-Substituted Bicyclo-Heptan-2-Amines at NMDA Receptors - Michelle Farbaniec; Adeboye Adejare; Shengguo Sun; Zeynep Ates-Alagoz; Boyenoh Gaye; Natalia Coleman (MDPI AG, 2013)
Several novel norcamphor derivatives were designed and synthesized as uncompetitive NMDA receptor antagonists at the phencyclidine (PCP) binding site. Such compounds have potential as ligands for understanding and possibly the treatment of several neurodegenerative disorders and other glutamate-dependent disorders. We examined the toxic effects of the compounds as compared with memantine, an NMDA receptor antagonist that is FDA approved for treatment of Alzheimer's disease, by testing these compounds on two cell lines: MDCK (to mimic blood brain barrier) and N2a (a neuronal cell line). The compounds showed toxicity profiles similar to those of memantine i.e., dose dependence above 100 μM and IC50 values above 150 μM for each cell line. It is known that the serum level of memantine under therapeutic conditions in patients is about 1 µM, indicting these compounds could have acceptable therapeutic indexes. 2-Phenyl-N-(2-(piperidin-1-yl) ethyl)bicyclo[2.2.1]heptan-2-amine (5a) was found to possess acceptable toxicity profiles in both cell lines. Interestingly, this was the compound identified as a good lead in our previous studies based on binding and anticonvulsant (MES) activity studies. It has thus emerged as an excellent lead compound for further studies.